Distance Learning During the Pandemic Era: Online Learning Experiences of State Madrasah Tsanawiyah Students During Covid-19 in Indonesia - Sihombing, Adison Adrianus; Fatra, Maifalinda (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Online learning policies serving as the answer to the world of education during the COVID-19 pandemic period raise some problems to students. They find it difficult to understand learning materials because the teacher's explanation is very limited, so many tasks and teachers cannot supervise the students. As a result, students are quickly getting bored with learning activities at home, they cannot directly meet their classmates; and this condition is getting worse due to the fact that their homes are less supportive to their learning activities. This research is aimed at studying the State Madrasah Tsanawiyah Students’ experiences during the Covid-19 pandemic era from March to July 2020. A descriptive qualitative analysis method was employed. The primary data were obtained from the results of observations and open questionnnaires sent to 42 the madrasah tsanawiyah students from Sidoarjo, Malang, Yogyakarta, Jakarta, Aceh, and Padang Panjang. The secondary data were taken from online news about the distance learning. It was found that the distance learning for madrasah tsanawiyah students was troublesome experiences due to inadequate facility and infrastructures in the internet quota, smart phones, laptops, and also unsupporting home environment and improper the teaching techniques. However, some students were happy with this distance learning because it may give them new experiences, learning with a laptop or a mobile phone is exciting, it may improve the literacy in technology, it is flexible in terms of time, and it is not necessary for them to go to schools. It is recommended that the government improve the quality of the internet services, give more internet assistance quota, and hold training for the teachers on online learning.